Which Body Would You Like to Have? The Impact of Embodied Perspective on Body Perception and Body Evaluation in Immersive Virtual Reality - Neyret, Solène; Bellido Rivas, Anna I.; Navarro, Xavi; Slater, Mel (Frontiers in Robotics and AI, 2020)
In this experiment, we wanted aimed to measure the conscious internal representation of one’s body appearance and allow the participants to compare it this to their ideal body appearance and to their real body appearance. We re-created a virtual representation of the internal image participants had of their own body shape. We also re-created a virtual body corresponding to the internal representation they had of their ir ideal body shape, and we built another virtual body based on their real body measures representing their real body shape. Participants saw the three different virtual bodies from an embodied first-person perspective and from a third-person perspective and they had to evaluate the appearance of those virtual bodies. We observed that female participants evaluated their real body as more attractive when they saw it from a third-person perspective, and that their level of body dissatisfaction was lower after the experimental procedure. We believe that third-person perspective allowed female participants to perceive their real body shape without applying the negative prior beliefs usually associated to the “self”, and that this resulted in a more positive evaluation of their body shape. We believespeculate that this method could be applied with patients suffering from eating disorders, by making their body perception more realistic and therefore improve their body satisfaction.